Functions of valency operators in Kamas - Klumpp, Gerson (Lingua Posnaniensis, 2016)
This article provides an account of the functional range of Kamas valency operators. Kamas is an extinct South Siberian language of the Samoyed branch of Uralic, which was in close contact with Turkic for many centuries. In the early 20th century, Kamas had two valency operators: (i) -Tə derived transitive from intransitive verbs as well as causative from transitive verbs; and (ii) -Ō derived intransitive from transitive verbs; in addition the intransitivizer, probably departing from pairs like edə- ‘hang up (tr.)’ > ed-ȫ- ‘hang (itr.)’, had acquired the function of specifying imperfective state-of-affairs, e.g. iʔbə- ‘lie down, lie’ > iʔb-ȫ- ‘lie’. The two markers may occur in combination in the order “increase-decrease” (-T-Ō), but not vice versa. While on the one hand the valency operators may be understood as verb derivation morphemes proper, i.e. verbs derived with the suffixes -Tə- and -Ō- are considered new lexical entries, their functional range also covers combinations with participles otherwise unspecified for voice. The valency decreaser -Ō occurs with participles of transitive verbs in order to specify P-orientation. The valency increaser -Tə has a variety of causative readings, among them causative-reflexive, causative-permissive, and causative-instrumental, and it also qualifies as a marker of control and/or characterizing activity. The discussion in this article is focused mainly on classificational issues.